2019
DOI: 10.1016/j.apcatb.2019.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced electrocatalytic production of H2O2 at Co-based air-diffusion cathodes for the photoelectro-Fenton treatment of bronopol

Abstract: Co, S, P)-decorated multiwalled carbon nanotubes (MWCNTs) have been synthesized following a hydrothermal route as electrocatalysts to manufacture large surface area airdiffusion cathodes with carbon cloth as substrate. The enhanced electrocatalytic H2O2 production as compared with Co-free MWCNTs cathodes was demonstrated in a 2.5-L prepilot plant with either a RuO2-based or boron-doped diamond (BDD) anode, accumulating between 2-and 3-fold greater H2O2 contents with the catalyzed cathode. The good stability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 51 publications
0
38
0
Order By: Relevance
“…In IrO2/air-diffusion cells, the optimum Fe 2+ catalyst concentration is in the range 27-55 mg L -1 . [8][9][10] Heterogeneous EF catalyzed with 0.5 g L -1 natural pyrite at initial pH 6.0 showed the lowest performance, attaining a fluoxetine concentration decay as low as 19%. Some authors have reported a fast pollutant removal by pyrite-EF, [30][31][32] but in those trials current was supplied once the spontaneous acidification and iron release had occurred.…”
Section: Resultsmentioning
confidence: 99%
“…In IrO2/air-diffusion cells, the optimum Fe 2+ catalyst concentration is in the range 27-55 mg L -1 . [8][9][10] Heterogeneous EF catalyzed with 0.5 g L -1 natural pyrite at initial pH 6.0 showed the lowest performance, attaining a fluoxetine concentration decay as low as 19%. Some authors have reported a fast pollutant removal by pyrite-EF, [30][31][32] but in those trials current was supplied once the spontaneous acidification and iron release had occurred.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the thin and porous structure of the membrane is beneficial for injected oxygen or air to seep through the pores and contact oxygen reduction reaction (ORR) active centers, which generates a large amount of H 2 O 2 . Ye et al [ 113 ] prepared Co-based air-diffusion cathodes to enhance the mass transfer function of O 2 , and they also found enhanced electrocatalytic H 2 O 2 production; moreover, the CE reached 100% at low current.…”
Section: Coupling Ms and Cathodic Eaops As An Integrated Technologmentioning
confidence: 99%
“…On the other hand, if considered a more advanced stage of the incomplete oxidation, other sorts of fragments may be found. Regarding the latest stage on the incomplete oxidation, organic acids of short-chair such as maleic acid, [14] oxalic acid, [15], and formic acid [16] have been identified for micropollutants in general. For this case, the stoichiometric oxidant quantity needed is far higher than half of that micropollutant quantity.…”
Section: Introductionmentioning
confidence: 99%